Mantle Anisotropy and Asthenospheric Flow Around Cratons in SE South America - Melo, Bruna Chagas de (2018)
Seismic anisotropy at continental regions, mainly at stable areas, gives important information about past and present tectonic events, and helps us in understanding patterns of upper mantle flow in a way not achieved by other methods. The measurement of shear wave splitting (SWS), at individual stations, from core refracted phases (such as SKS phases), indicates the amount and orientation of the seismic anisotropy in the upper mantle. Previous studies of SWS in South America concentrated mainly along the Andes and in southeast Brazil. Now we add extra measurements extending to all Brazilian territory, especially in the Pantanal and Paraná-Chaco basins, as part of the FAPESP 3-Basins Thematic Project. The results from both temporary deployments and from the Brazilian permanent network provide a more complete and robust anisotropy map of the South America stable platform. In general the fast polarization orientations have an average E-W orientation. Significant deviations to ESE-WNW or ENE-WSW are observed in many regions. We compare our results with different anisotropy proxies: absolute plate motion given by the hotspot reference frame HS3-NUVEL-1A, a recent model of time dependent upper mantle flow induced by the Nazca plate subduction, global anisotropy from surface wave tomography, and geologic trends. We observe a poor correlation of the anisotropy directions with geological trends, with the exception of a few stations in northern Brazil and a better correlation with the mantle flow model. Therefore, our observed anisotropy is mainly due to upper-mantle flow, with little contribution from frozen lithospheric anisotropy. Also, deviations from the mantle flow model, which includes a thicker lithosphere at the Amazon craton, are mainly due to flow surrounding cratonic nuclei not used in the model: the keel of the São Francisco craton and a possible cratonic nucleus beneath the northern part of the Paraná Basin (called Paranapanema block). Large delay times at the Pantanal Basin may indicate a stronger asthenospheric channel, a more coherent flow, or a thicker asthenosphere. Small delays beneath the northern Paraná Basin and central Amazon craton may indicate thinner anisotropic asthenosphere.